2016
DOI: 10.4238/gmr.15038721
|View full text |Cite
|
Sign up to set email alerts
|

An improved DNA marker technique for genetic characterization using RAMP-PCR with high-GC primers

Abstract: ABSTRACT. Random amplified polymorphic DNA (RAPD) is a widely used molecular marker technique. As traditional RAPD has poor reproducibility and productivity, we previously developed an improved RAPD method (termed RAMP-PCR), which increased the reproducibility, number of bands, and efficiency of studies on polymorphism. To further develop the efficiency of this method, we used high-GC content primers for improved RAMP-PCR with DNA samples from Lonicera japonica. Comparison of amplification profiles obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The resolution and production of RAPD are greatly increased by prolonging the RAMP time from the stage of annealing to extension in PCR [ 18 , 19 ]. Recently, the technique was modified using high-GC content primers to improve the effectiveness of the RAPD method (high-GC RAMP-PCR technique) [ 20 ]. This improved RAPD successfully increased the number of RAPD bands produced from a given DNA sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The resolution and production of RAPD are greatly increased by prolonging the RAMP time from the stage of annealing to extension in PCR [ 18 , 19 ]. Recently, the technique was modified using high-GC content primers to improve the effectiveness of the RAPD method (high-GC RAMP-PCR technique) [ 20 ]. This improved RAPD successfully increased the number of RAPD bands produced from a given DNA sample.…”
Section: Discussionmentioning
confidence: 99%
“…Using improved RAPD with high-GC content primers, we found that the average number of bands per primer increased from 6.41 to 15.04 in comparison to regular RAPD with standard primers. The average number of polymorphisms per primer was also increased from 4.647 to 10.22 [ 20 ]. Thus, we can produce more polymorphic bands using less RAPD primers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These gene-rich regions bring significant biological information about the genome. Cheng et al (2016) and Wei et al (2016) worked with high GC-content, aiming the development of new molecular markers, highlighting the importance of working with gene-rich regions. Table 1 shows the information for each sequence obtained at the site of the NCBI.…”
Section: Gc-contentmentioning
confidence: 99%